Prolong Fever with Murmur in Heart in a patient with History of Intravenous Drug Abuse - A Case Report - Islam, KK; Kar, N; Ullah, M (Cardiovascular Journal, 2010)
Right sided endocarditis accounts for 10% of all IE in population based surveys and a higher proportion of IE in injection drug users. Among injection drug users presenting with fever, 13% will have Echocardiographic evidence of IE. Staphylococcal endocarditis in injection drug users is now the dominant form of the disease in many urban communities where there is a high incidence of injection drug use and homelessness. Modern echocardiographic techniques have considerably augmented our ability to diagnose IE and to understand its natural history. Despite this, there are many areas in which our understanding of right sided IE remains incomplete. Keywords: Infective endocarditis; Tricuspid valve IVDU DOI: 10.3329/cardio.v3i1.6436 Cardiovasc. j. 2010; 3(1): 101-103